Bugis and Madura migration in nusantara: Religiosity, harmony, and identity from Eastern Indonesia - Suyatno, Ladiqi; Ismail Suardi, Wekke; Reevany, Bustami (2019)
The Buginese and Madurese are well known as fierce sailors and are openhearted ethnics in Indonesia. It seems that they have their typical characters and identities compared to the other ethnics in Indonesia. Their characters and identities become part of their life, including in economic, social customs or even when they immigrated to a new place. This phenomenology study tried to explain the behavior of Buginese and the people of Madurese who immigrated to Papua. The study also would seek to explore beyond migration of the Bugis and Madurese in Papua. This article was conducted in Papua to assess the patterns of migration and community interaction of Bugis and Madurese with other communities. The study findings revealed that Buginese and Madurese seem similar among others in terms of economic activity, mastery in the field of politics, and social role in the community. Besides, with their capacity, it has a role in religious activities which they always carry out in their environment. By not making it as a mission of deployment religious activities, but rather only to defend their religious understanding in a way that it would be limited just to the internal environment. It seems both the Buginese and Madurese firmly have a connection to the Islamic identity factors that are part of their religious expression.